Pemetaan Lahan Kritis di Kecamatan Kuta Selatan Kabupaten Badung - Manalu, Tugma Jaya; Sunimbar, Sunimbar; Haryani, Poppy; Sejati, Martina Ayu (Jurnal Geografi, 2025)
Tourism development in South Kuta Subdistrict has driven an increase in construction activities for residential needs, infrastructure, and supporting tourism facilities. These activities have led to the growing potential of critical land in the South Kuta Subdistrict. This study aims to determine the distribution and area of critical land in South Kuta Subdistrict. The data used in this study includes administrative maps, forest area maps, erosion maps, land use maps, and slope maps. A few methods used included overlay and scoring of maps based on parameters. The study results showed that the non-critical land area is 4.212,16 ha, potentially critical land is 2.601,51 ha, moderately critical land is 3.197,24 ha, and critical land is 102.08 ha. The non-critical land classes tends to dominate the northern part, while the critical land is more spread out in the southern part. The northern part is the area that developed earlier with more structured planning, such as the Nusa Dua area. Critical land requires prioritized handling by implementing appropriate conservation techniques to prevent further damage. Conservation efforts that can be made include planting ground cover plants to prevent surface erosion, and the government’s role is essential in enforcing building permits on critical lands.